Az „Sz Programpont" : Teleki Pál egy kevésbé ismert reformtervezete - Nyári, Gábor (Közép-Európai Közlemények, 2016)
The present study strives to examine a less know reform plan, the so-called „SZ agenda” from the second term (1939–1941) of PM Pál Teleki. The file labeled as „highly classified”, which turned up in the secretary of the foreign office, Elemér Újpétey’s legacy, encompasses a series of papers comprising a complete plan to reform the public administration, the government, and the economy. None of these papers indicates neither the name of its author nor the date of its creation, nonetheless it is fair to assume that they were laid down around November/December of 1940, and that the Service for National Policy, which used to orchestrate Teleki’s secret domestic actions, was hugely involved in their making. The most important piece of these papers concentrates on the so-called State Staff, which, at its core, would have been an organization akin to the Council of Ministers assisting the PM and the government. An organization of this kind could have worked as a kind of shadow government in the event of a possible German occupation. By and large, these papers reveal that the outlined reforms were interrelated with Teleki’s corporatist ideas, nevertheless their paramount importance was to beef up an independent and sovereign Hungary first and foremost vis-à-vis the Third Reich. It is uncharted, which stage of its realization the „SZ agenda” arrived at, but it is fairly feasible that the main hurdle to its implementation was Pál Teleki’s death on April 3, 1941.